2014
DOI: 10.4293/108680813x13693422520765
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fellowship During Single-Incision Laparoscopic Cholecystectomy

Abstract: Adoption of single-incision laparoscopic cholecystectomy during fellowship training is safe and feasible; however, longer operative times are expected during the teaching process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Patient outcomes after surgical procedures performed by surgical trainees have been previously studied. A number of studies have reported that operative times tend to be longer with the participation of trainees, which is consistent with the results of this trial .…”
Section: Discussionsupporting
confidence: 91%
“…Patient outcomes after surgical procedures performed by surgical trainees have been previously studied. A number of studies have reported that operative times tend to be longer with the participation of trainees, which is consistent with the results of this trial .…”
Section: Discussionsupporting
confidence: 91%